Favourable approach that influence autism students learning language process - Hashim, Suhaizal; Ismail, Mohd Erfy; Sa’adan, Nadzrah; Che Lah, Noor Hidayah; Ismail, Irwan Mahazir (Science Research Society, 2021)
Education is important for all, including those students with special needs.In this context, learning process for students with special needsis certainly different from normal students, with special developed curriculum, as well as special skills for teachers are devotedfor teaching specific courses.This study investigatesthe special education teachers’approach in teaching phonics of the language (i.e. Bahasa Melayu)for autism students, focusing on three elements; namely learning module, oral language and multimedia application. A survey study was designed using questionnaire involving 42 special education teachers from primary schools in the Southern Peninsular of Malaysia.Descriptive analysis were used to obtain percentage, mean, and standard deviation. The results;a moderate level application of the module (M = 3.43, SD = 0.654) and the oral language (M = 3.64, SD = 0.570), but a high level of the multimedia application(M = 4.14, SD = 0.612). The multimedia elements wasthe most favorable approach in the teaching and learning process of autism students.The implication;more special design of a multimedia materials are needed for teaching phonics for language learning to help autism students to speaking correctly.